The effects of a surgical mask and an N95 mask on intelligibility of explicit and ambiguous speech produced in the operating room environment - Ishido, Hidemi; Oishi, Rieko; Yamazaki, Yuki; Inoue, Satoki (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
Purpose We investigated the effects of a surgical mask and an N95 mask on speech intelligibility using explicit and ambiguous sentences in Japanese. In addition, the effects of background noise specific to an operating room environment on the speech intelligibility of these sentences were also investigated. Methods We created 20 sets of five sentences; 10 sets consisting of explicit words, and 10 containing ambiguous words. Each set was recorded by a speaker while wearing a surgical mask or an N95 mask, combined with a face shield. A total of four combinations of speech data were created. Each subject was asked to listen to one set from each of the four combinations and write down the speech. The test was performed in normal background noise as well as in noise levels of 50, 60, and 70 dB. Results Twenty-eight volunteers were included in this study. In the tests for explicit sentences, intelligibility of speech with an N95 mask was significantly lower than that with a surgical mask in the presence of 60 dB noise. As for explicit sentences produced with a surgical mask, intelligibility was significantly decreased in the presence of 70 dB noise. Regarding explicit sentences produced with an N95 mask, intelligibility was significantly decreased in the presence of 60 and 70 dB noise. In the tests for ambiguous sentences, intelligibility of speech produced with an N95 mask was not significantly lower than that with a surgical mask at all noise levels. As for ambiguous sentences produced with a surgical mask, no significant decrease in intelligibility was observed at any noise level. Regarding ambiguous sentences produced with an N95 mask, intelligibility was significantly decreased in the presence of 60 and 70 dB noise. Conclusion Speech intelligibility was impaired both with a surgical mask and an N95 mask in the normal background noise specific in an operating room during surgery, even if the speech consisted of explicit words. The impairment of speech intelligibility was significantly exacerbated with the use of ambiguous language and in the background noise typical in an operating room environment. Speech intelligibility was further reduced with the use of an N95 mask. Trial Registration Registered at the University Hospital Medical Information Network Clinical Trials Registry on March 7, 2023 (UMIN R000050373).